Burnout among secondary teachers amid the new normal: Case in Ormoc City, Philippines - Malquisto, Irene R.; Casinillo, Leomarich F.; Salabao, Analita A. (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2023)
The new normal has shifted high school teachers’ jobs from face-to-face to modular distance learning which requires more paperwork. This research article investigated job burnout among secondary teachers in Ormoc City Division, Leyte, Philippines, and elucidated the statistically significant factors affecting it. Primary data were gathered from a simple random sample of 132 high school teachers in the City of Ormoc. To summarise the acquired survey results, typical descriptive metrics such as frequency tables, percentages, mean average, and standard deviation were used to summarize the gathered survey data. The Chi-square test of independence was employed to capture the different factors influencing job burnout. The findings revealed that, on average, secondary teachers are “highly burnout” in modular and distance learning amidst the COVID-19 pandemic setup. The Chi-square test showed that marital status and department/school assignment are the factors influencing teachers’ burnout levels. In particular, the cross-tabulation of marital status and burnout category revealed that married teachers are mostly highly burnout. Finally, responsibilities and duties in their household contribute to the teachers’ working stress and tiredness. Furthermore, different schools have varying job assignments, with some schools assigning heavier loads, resulting in severe teacher burnout. According to the report, school leaders should prioritize teachers’ well-being by reducing their responsibilities and implementing leisure school activities to alleviate stressful circumstances.